Biological Enhancement of Healing with Kartogenin Injection at the Tendon-to-Bone Interface in a Rat Rotator Cuff Tear Model - Kim, Dong Hyun; Min, Seung Gi; Kim, Hun-Min; Choi, Jin-Hyun; Lee, Hyun Joo; Park, Kyeong Hyeon; Yoon, Jong Pil (The Korean Journal of Sports Medicine, 2020)
Purpose: The purpose of this study was to investigate the effects of kartogenin (KGN) on the tendon-bone interface in a rat rotator cuff tear model. Methods: Twenty male rats were divided into two equal groups; group 1 (repair only) and group 2 (KGN single injection). A rat rotator cuff rupture model was prepared, and KGN (500 μM) was injected into the repair site. The specimens were collected after 8 weeks, and biomechanical and histological analyses were performed. We assessed the healing quality of the tendon-to-bone repair site using six aspects of tendon tissue. The histological findings were classified semiquantitatively into four grades (grade 0, the poorest appearance; grade 1, poorer; grade 2, better; and grade 3, marked regeneration). Results: Group 2 showed a higher mean ultimate load to failure than the control group (group 1: 25.78±31.38 N, group 2: 55.64±36.02 N; p=0.011). On histological analysis, group 2 exhibited a significantly greater total score (group 1: 7.20±2.14, group 2: 9.50±1.84; p=0.019), collagen fiber continuity (group 1: 1.20±0.42, group 2: 1.70±0.48; p=0.024), and collagen fiber density (group 1: 1.50±0.52, group 2: 2.20±0.63; p=0.080). Metachromasia were more intense in group 2 than in the control group. Conclusion: A single injection of KGN reinforces biomechanical strength and the formation of collagen and fibrocartilage at the tendon-to-bone interface in a rat rotator cuff tear model. KCI Citation Count: 0